Bacterial diversity and community in Qula from the Qinghai–Tibetan Plateau in China - Zhu, Yan; Cao, Yingying; Yang, Min; Wen, Pengchen; Cao, Lei; Ma, Jiang; Zhang, Zhongmin; Zhang, Weibing (PeerJ, 2018)
Qula is a cheese-like product usually prepared with unpasteurized yak milk under open conditions, with both endogenous and exogenous microorganisms involved in the fermentation process. In the present study, 15 Qula samples were collected from five different regions in China to investigate the diversity of microbial communities using high-throughput sequencing targeting the V3–V4 region of 16S rRNA gene. The bacterial diversity significantly differed among samples of different origins, indicating a possible effect of geography. The result also showed that microbial communities significantly differed in samples of different origin and these differences were greater at the genus than the phylum level. A total of six phyla were identified in the samples, and Firmicutes and Proteobacteria had a relative abundance >20%. A total of 73 bacterial genera were identified in the samples. Two dominant genera (Lactobacillus and Acetobacter) were common to all samples, and a total of 47 operational taxonomic units at different levels significantly differed between samples of different origin. The predicted functional genes of the bacteria present in samples also indicated differences in bacterial communities between the samples of different origin. The network analysis showed that microbial interactions between bacterial communities in Qula were very complex. This study lays a foundation for further investigations into its food ecology.
Keywords: Illumina MiSeq sequencing; Qula; Bacterial community